Faecal matter as inoculum for in vitro gas production - Pandian, C.S.; Reddy, T.K.; Sivaiah; Blümmel, Michael; Ramana Reddy, Y. (Diva Enterprises Private Limited, 2016)
Rumen inoculum (RI) was replaced by fresh faecal inoculum (FI) on microbial nitrogen equivalent. Microbial nitrogen in FI was estimated as total N minus N bound to neutral detergent in stover-fed bullocks and 2.8 gram of FI provided similar (6.4 mg) microbial N to that of 10 ml of RI. Extent and rate of in vitro gas production (IVGP) of 200 mg of standards of sorghum stover and hay was measured in syringes containing a total of 30 ml of medium with 2.5, 3.0, 3.5 or 4.0 g FI and compared with incubations containing 10 ml of RI in 30 ml of medium. Faecal concentration had little effect on extent of gas production but rate of gas production increased from 2.5 to 3.5 g but decreased from 3.5 to 4.0 g. However, rates of gas production in 3.5 g of FI were only about 60–65% of the rates observed with RI. Ranking between FI and RI agreed for rates but not always for extents of gas production. To conclude, similar amounts of microbial N provided by either rumen or faecal inoculum do not result in similar degradative potential in vitro. However, in the present scenario, FI can be used as an alternative inoculum to RI for IVGP technique.